Braillín, the doll that favors the social integration playing. (Journal of Parents and Teachers, 2014)
The ONCE and the Research Association of the Toy Industry have created a doll that promotes social integration through play. It favors the acceptance of diversity and brings the Braille code to children with and without visual impairment.
Keywords: Blindness; Braille; social integration; toy; doll; diversity.